2007
DOI: 10.1021/jf071903f
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Lowering Mechanism of Soybean Protein Hydrolysate

Abstract: Numerous attempts have been made to find the mechanism and component of the cholesterol lowering activity of soybean. In this study, it was proved that the peptides in soybean protein hydrolysate (SPH) made by certain proteases have a hypocholesterolemic effect. Among the mechanisms suggested, that is, blockage of bile acid and/or cholesterol absorption, inhibition of cholesterol synthesis, and stimulation of low-density lipoprotein receptor (LDL-R) transcription, SPH appeared to stimulate LDL-R transcription.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 25 publications
2
70
1
2
Order By: Relevance
“…3 Our studies regarding peptide-induced physiological functions also revealed that basic and/or hydrophobic small peptides, such as Trp-His, exerted vasorelaxation effects in the aorta through the retardation of intracellular Ca 2+ -signaling pathways, [4][5][6] and could be absorbed intact into the blood system via intestinal peptide transporter 1. [7][8][9] Peptides, which are condensed amino acids, have many members in their polymeric series, e.g., >400 di-peptides and >8000 tri-peptides, and simple and convenient assays for bioactive small peptides in food hydrolysates or natural materials are required in the food industry.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…3 Our studies regarding peptide-induced physiological functions also revealed that basic and/or hydrophobic small peptides, such as Trp-His, exerted vasorelaxation effects in the aorta through the retardation of intracellular Ca 2+ -signaling pathways, [4][5][6] and could be absorbed intact into the blood system via intestinal peptide transporter 1. [7][8][9] Peptides, which are condensed amino acids, have many members in their polymeric series, e.g., >400 di-peptides and >8000 tri-peptides, and simple and convenient assays for bioactive small peptides in food hydrolysates or natural materials are required in the food industry.…”
Section: Introductionmentioning
confidence: 82%
“…1); in turn, the sulfonated or cation-exchange/reversed phase column must be of benefit for the retention of basic peptides that often show some preventive physiological effects against lifesyle-related diseases. [1][2][3][4][5][6]16 The use of a cation-exchange/reversed phase column was attempted in the separation of acetylated oligo-(>10 mer) peptides, and a sufficient separation was achieved by hydrophilic interaction (HILIC) chromatography with increased hydrophilicity and salt (NaClO4) concentrations. 20 However, these reports were limited to the separation of terminal-protected or hydrophobic oligo-peptides, and did not include the separation of non-protected small (di-/tri-) peptides with varying pI profiles.…”
Section: Characteristics Of a Sulfonated Ethylstyrene-divinylbenzene mentioning
confidence: 99%
“…Several studies were conducted, particularly with milk proteins [9,10], eggs [11,12], and muscle proteins from pigs [13], cattle [14], poultry [15], and fish [16]. BAPs have been obtained from vegetable proteins such as soybeans [17,18], lentils, chickpeas, peas, beans, and oilseeds such as canola and flaxseed [8]. As to fish, the fishing industry has shown much interest in obtaining bioactive peptides and hydrolysates from fishery by-products, including carcasses and viscera of aquatic animals, of very low commercial value.…”
Section: Production and Processing Of Bioactive Peptides Derived Frommentioning
confidence: 99%
“…According to Undenigwe and Aluko [6] protein sources of hypocholesterolemic and hypolipidemic peptides include soy protein [17], milk proteins [105], egg white proteins [106], and fish proteins [107]. Enzymatic hydrolysis can also produce peptides capable of reducing TAG with reduction of lipidemia [108].…”
Section: Antihyperlipidemic and Antithrombotic Peptidesmentioning
confidence: 99%
“…The average molecular weight of SP is about 3-10 kDa, and it is characterized to have a high glutamic acid content. Reported actions of SP include a cholesterol-inhibitory effect, 13) a weight loss effect, 14) an anti-fatigue effect, 15) and an antihypertensive effect. 16) Low molecular weight SP (LSP), which is a SP that has been further broken down, has an average molecular weight of about 500-1,000 Da; like SP, it has a high glutamic acid content.…”
mentioning
confidence: 99%